Factors Affecting Dividend Policy: Study on Food and Beverage Manufacturing Sector Companies Listed on the Indonesia Stock Exchange - Pradika, Riri; Rediyono, Rediyono (International Journal of Economics and Financial Issues, 2022)
The distribution of dividends to the company to investors is determined through a dividend policy. Factors that can affect dividend policy include profitability, liquidity, company growth rate, and company size. This study aims to determine the significance of the company's growth rate and the size of the company to the dividend policy of manufacturing companies on the Indonesia Stock Exchange for the period 2016-2020. The population in this study is a manufacturing company in the food and beverage industry sector listed on the Indonesia Stock Exchange for the period 2016-2020, for total of 17 companies. This study used multiple linear regression methods to test hypotheses with a statistical analysis tool in the form of SPSS Version 21 software. The growth rate, Profitability, Solvency and Size of the Company have a significant effect simultaneously on deviden policy (Study on Food and Beverage Manufacturing Sector Companies listed on the Indonesia Stock Exchange from 2016 to 2020). The results of the analysis showed that profitability, liquidity, company size are positive and significant to dividend policy while the results of the analysis of the company's growth rate have a negative and significant effect on dividend policy in manufacturing companies on the Indonesia Stock Exchange.